Research ethics challenges during the COVID-19 pandemic: what should and what should not be done - Atif Abdulhamid Katib (Journal of Ideas in Health, 2020)
This article is directed primarily at how clinical trials can be ethically conducted in the midst of the current global COVID-19 pandemic. We explain why ethical issues are more complicated than they once were. Furthermore, we discuss the relevant parties` roles in protecting participants` rights and in keeping basic research ethics of justice, respect, equity, and beneficence strongly implemented on the ground. References Moorthy V, Restrepo H, Preziosi MP, Swaminathan S. Data sharing for novel coronavirus (COVID-19). Bull World Health Organ. 2020; 98: 150. http://dx.doi.org/10.2471/BLT.20.251561 Angus DC. Optimizing the trade-off between learning and doing in a pandemic. Epub ahead of print, 2020. https://doi.org/10.1001/jama.2020.4984)JAMA Park YR, Koo H, Yoon YK, Park S, Lim Y-S, Baek S, et al. Expedited Safety Reporting to Sponsors Through the Implementation of an Alert System for Clinical Trial Management at an Academic Medical Center: Retrospective Design Study. JMIR Med Inform. 2020;8(2): e14379. https://doi.org/2196/14379. Bae J, Lee J, Jang Y, Lee Y. Development of simulation education debriefing protocol with faculty guide for enhancement clinical reasoning. BMC Med Educ. 2019;19(1):197. https://doi.org/10.1186/s12909-019-1633-8. Cox EM, Edmund AV, Kratz E, Lockwood SH, Shankar A. Regulatory Affairs 101: Introduction to Expedited Regulatory Pathways. Clin Transl Sci. 2020;13(3):451‐ https://doi.org/10.1111/cts.12745. Epub 2020 Feb 6. Rivenbark JG, Ichou M. Discrimination in healthcare as a barrier to care: experiences of socially disadvantaged populations in France from a nationally representative survey. BMC Public Health. 2020;20(1):31. https://doi.org/1186/s12889-019-8124-z Arsenijevic J, Tummers L, Bosma N. Adherence to Electronic Health Tools Among Vulnerable Groups: Systematic Literature Review and Meta-Analysis. J Med Internet Res. 2020;22(2): e11613. https://doi.org/2196/11613 Plotkin S, Robinson JM, Cunningham G, Iqbal R, Larsen S. The complexity and cost of vaccine manufacturing: An overview. Vaccine. 2017;35(33):4064–71. https://doi.org/1016/j.vaccine.2017.06.003. Deming D. Do extraordinary claims require extraordinary evidence? Philosophia (Ramat Gan). 2016;44(4):1319‐ https://doi.org/10.3389/fpsyg.2011.00117